Playing out diplomacy: gamified realization of future skills and discipline-specific theory - Kruskopf, Milla; Ketonen, Elina E.; Mattlin, Mikael (European political science, 2021)
Future horizons, shaped by unpredictable ecosystems and exponential automation, require discipline-specific as well as transdisciplinary skills to navigate. In the context of political science education, negotiation simulations, for example in the form of board games, can aid in developing both. As a plausibility probe for wider investigations, we set out to research whether an International Relations course concept utilizing the classical board game Diplomacy with pedagogically altered rules and gaming conditions enhances students’ ( n = 23) understanding of discipline-specific knowledge and future skills. We utilized a conceptual pre-post measure as well as free-form learning diaries to investigate development in participants’ conceptual understanding and future skills along the course. The results tentatively suggest quantifiable and qualitatively observable changes in the discipline-specific conceptual, as well as more broad-based competence level. The gamified learning environment provided students with an activating and engaging learning environment that better acquainted them not only with discipline-specific theory, but more importantly, also with skills regarded important for their future.